Analysis and Modelling of Advanced Structures and Smart Systems (Advanced Structured Materials,, 2018)
This book presents selected papers presented at the 8th International Conference "Design, Modeling and Experiments of Advanced Structures and Systems" (DeMEASS VIII, held in Moscow, Russia in May 2017) and reflects the modern state of sciences in this field. The contributions contain topics like Piezoelectric, Ferroelectric, Ferroelastic and Magnetostrictive Materials, Shape Memory Alloys and Active Polymers, Functionally Graded Materials, Multi-Functional Smart Materials and Structures, Coupled Multi-Field Problems, Design and Modeling of Sensors and Actuators, Adaptive Structures.